EFL Teacher Professionalism and Identity: Between Local/Global ELT Tensions - Julio Cesar Torres-Rocha (Asociación Colombiana de Profesores de Ingles, 2019)
This article of reflection considers socio-political issues such as linguistic imperialism, native speakerism, English as an International language, and appropriate teaching methodologies, which are currently contentious issues in the ELT community. Framed within a critical approach of applied linguistics, these issues are addressed in three sections (global/local tensions, teacher professional identity, and a new EFL professional identity) in order to argue that a dynamic, shifting, and multifaceted perspective of a globally-minded EFL teacher professional identity is needed so that Colombian EFL professionals can define or redefine their own identities in taking an informed and critical political stance.